Determinants of the exit value in European venture capital-backed technology startups. Issue 7 (21st December 2021) - Montanaro, Benedetta; Cavallo, Angelo; Giudici, Giancarlo; Ghezzi, Antonio
Abstract : Purpose: This study aims to analyze the impact of different exit alternatives, investor presence and founders' human capital on the exit value of European venture capital (VC)-backed high technology startups. Design/methodology/approach: The empirical analysis is based on a sample of 107 European firms that obtained an exit through Merger&Acquisition (M&A) or an initial public offering (IPO) between 2010 and 2017, backed by VC investors. Findings: This study provides empirical evidence on how different exit alternatives, investor heterogeneity and founders' human capital may affect the exit value of European VC-backed startups. Exiting through an IPO and retaining a larger equity stake are positively correlated with the exit value. The presence of business angels and non-governmental VC firms is associated with larger valuations. Founders' previous education was positively correlated with the exit value. Originality/value: Exit strategies in technology startups are essential to capitalize investors' efforts and reinvest cash into new ventures, supporting the development of entrepreneurial ecosystems and countries' competitiveness. The results of this study provide interesting hints for policymakers and contribute to an in-depth understanding of the drivers of exit valuation for startups.